2018
DOI: 10.1137/17m1118981
|View full text |Cite
|
Sign up to set email alerts
|

Spectrahedral Shadows

Abstract: We show that there are many (compact) convex semi-algebraic sets in euclidean space that are not spectrahedral shadows. This gives a negative answer to a question by Nemirovski, resp. it shows that the Helton-Nie conjecture is false.2010 Mathematics Subject Classification. Primary 90C22, secondary 14P05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 30 publications
(40 reference statements)
0
30
0
Order By: Relevance
“…In 2009, Helton and Nie [5] conjectured that conversely every convex semialgebraic set is a spectrahedral shadow. This conjecture was recently disproved by the author [28]. In the present paper, however, we prove the existence of a semidefinite representation for the closed convex hull of any one-dimensional semialgebraic set in R n .…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…In 2009, Helton and Nie [5] conjectured that conversely every convex semialgebraic set is a spectrahedral shadow. This conjecture was recently disproved by the author [28]. In the present paper, however, we prove the existence of a semidefinite representation for the closed convex hull of any one-dimensional semialgebraic set in R n .…”
mentioning
confidence: 61%
“…Indeed, for every semialgebraic set K ⊆ R n of dimension at least two, there exists a polynomial map ϕ : R n → R N (for some N ≥ 1) such that the closed convex hull of ϕ(K) in R N has no semidefinite representation. This is proved in [28].…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Remark 3.3. Definition 3.2 expresses R f as a union of spectrahedral shadows [17,19]. To see this, fix a point x in V f .…”
Section: From Semidefinite To Quadratic Optimizationmentioning
confidence: 99%
“…In particular, it is known that the conjecture is true in dimension 2 [Sch12]. The conjecture has been recently disproved by Scheidered, who showed that the cone of positive semidefinite forms cannot be expressed as a projection of spectrahedra, except in some particular cases [Sch16]. A comprehensive list of references can be found in this work.…”
Section: Introductionmentioning
confidence: 88%